The effect of brand value on economic growth: A multinational analysis - Nuriye Zeynep Ökten; Elif Yolbulan Okan; Ünal Arslan; Mustafa Özgür Güngör (European Research on Management and Business Economics (ERMBE), 2019)
In the 21st century, the growth of each country's economy is now mostly influenced by the assets based on physical or non-physical grounds. These invisible assets are, as explained by various studies, supporting that they are one of the most important driving forces in the country's economy to accelerate growth. However, there is still a need for a more detailed research regarding the emergence and the impetus of this subject. This study aims to measure the effect of the intentional invisible asset on the growth of a country's economy. The correlation between the growth rates of 38 countries between 2008 and 2017 and the Top 500 brand values was analyzed for short and long-term by using the ARDL co-integration analysis. The effect of investing in national brands and increasing brand values of the country was observed to be negative in the short-term, but positive on the long-term with regards to the country's economic growth.
Keywords: 650; Economic growth; Intangible assets; Brand value; International business